2022
DOI: 10.3389/fpls.2022.800768
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatic Transcriptome Analysis of Self-Incompatible and Compatible Pollination in Corylus heterophylla Fisch. × Corylus avellana L.

Abstract: Self-incompatibility (SI) protects plants from inbreeding depression due to self-pollination and promotes the outcrossing process to maintain a high degree of heterozygosity during evolution. Corylus is an important woody oil and nut species that shows sporophytic SI (SSI). Yet the molecular mechanism of SI in Corylus remains largely unknown. Here we conducted self- (“Dawei” × “Dawei”) and cross-pollination (“Dawei” × “Liaozhen No. 7”) experiments and then performed an RNA-Seq analysis to investigate the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Corylus may harbor a novel SSI molecular mechanism that differs from Brassica (Hill et al, 2021;Hou et al, 2022). The analysis presented here provides additional evidence for independent evolution of a sporophytic self-incompatibility mechanism that is unique to Corylus, and not shared by other members of the Betulaceae, nor model species of SSI such as Brassica oleracea.…”
Section: Cross-genus Level Analysismentioning
confidence: 64%
See 1 more Smart Citation
“…Corylus may harbor a novel SSI molecular mechanism that differs from Brassica (Hill et al, 2021;Hou et al, 2022). The analysis presented here provides additional evidence for independent evolution of a sporophytic self-incompatibility mechanism that is unique to Corylus, and not shared by other members of the Betulaceae, nor model species of SSI such as Brassica oleracea.…”
Section: Cross-genus Level Analysismentioning
confidence: 64%
“…The locus regulating sporophytic self-incompatibility (SSI) in hazelnut has been fine-mapped in C. avellana (Hill et al, 2021) and C. heterophylla x C. avellana interspecific hybrids (Hou et al, 2022). These studies identified three MIK2 homologues believed to be responsible for SSI in these two Corylus species.…”
Section: Phylogenetic Analysis Of Sporophytic Self-incompatibilitymentioning
confidence: 99%
“…It is a rather a complex genetic network containing multiple genes. It has been reported that TFs play an important role in plant biological processes by regulating relative gene expression, including plant growth, synthesis of secondary metabolites ( Song et al., 2022 ), stress/stimulus responses ( Luo et al., 2022 ), flower senescence ( Ji et al, 2022 ), SI reaction processes ( Hou et al., 2022 ), pollen tube growth ( Zou et al., 2010 ) and other important biological processes. In tomato, progressive mutation of TFs led to a transition from outcrossing to self-pollination ( Benoit, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sequences for three S-locus genes (MIK3 homologues) reported by Hou et al (2022) were obtained from the transcriptome reported in Zhao et al (2021). NCBI-BLAST v2.6.0+ (Altschul et al, 1990) was used to identify homologous sequences in all Corylus species, as well as B. pendula, M. domestica and Brassica oleracea.…”
Section: Phylogenetic Analysis Of Sporophytic Self-incompatibility (Ssi)mentioning
confidence: 99%